2005
DOI: 10.1097/01.ccm.0000150650.70142.e9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airway pressure display on interobserver agreement in the assessment of vascular pressures in patients with acute lung injury and acute respiratory distress syndrome*

Abstract: Paw display is a simple, inexpensive method to facilitate the identification of end-expiration that can significantly improve interobserver agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In the FACTT trial4 in 2005, the two approaches were combined, demonstrating promising results. However, we found that there are some disadvantages in this approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the FACTT trial4 in 2005, the two approaches were combined, demonstrating promising results. However, we found that there are some disadvantages in this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group was established as described in the FACTT trial 4. The detailed PAWP measurement procedure was established, and systemic training of all of the staff members was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of microvascular obstruction there may be localised shunting of blood around areas of Central venous pressure (CVP) measurements do not directly measure circulating volume [94] and have variable reliability [95]. CVP measurements have been reported as being low in some studies [80] and not in others [93].…”
Section: Sequestrationmentioning
confidence: 99%